Heavy Drinkers' Perspectives on Minimum Unit Pricing for Alcohol in Scotland: A Qualitative Interview Study. (July 2016) - O'May, Fiona; Gill, Jan; Black, Heather; Rees, Cheryl; Chick, Jonathan; McPake, Barbara
The irrefutable consequence of Scottish excessive alcohol consumption has prompted implementation and proposal of alcohol policy measures. The purpose of this study is to explore with heavy drinkers their awareness of and identify potential implications of policy introducing alcohol minimum unit pricing (MUP). Face-to-face semi-structured interviews were conducted with drinkers with alcohol-related harm ( n = 20; 15 males, five females; aged 34 to 67 years old) in Scotland's two largest cities (drinkers were participants within a larger quantitative study, through attendance for treatment for alcohol-related harms at National Health Service [NHS] centers). Median weekly consumption among participants was 130.7 units (range: 28-256.3 U.K. units). Views regarding the impact of increased alcohol prices, through MUP, were mixed. While some drinkers indicated potential reduction in intake, thus possibly reducing alcohol harms in the long term, the expected, or even desired, from a public health perspective, effects on consumption and associated harms might not be fully realized in this group. To mitigate possible unintended short-term detrimental effects of MUP on the most vulnerable, careful planning and appropriate resourcing may be required prior to implementation.